Diagnostic-treatment continuum of prolonged grief disorder: modern perspectives on clinical criteria and intervention principles - Khaustova Олена; Skrynnyk Ольга (Psychosomatic Medicine and General Practice, 2025)
Objective War brings with it a lot of grief and bereavement, which is unpredictable neither in scope nor in time. Among them, the most difficult is the death of a loved one. With the beginning of the war, the problem of bereavement and grieving as a reaction to bereavement becomes actual. If the individual does not cope with the bereavement, the grieving process is prolonged and transforms into prolonged grief disorder (PGD). The significant spread of PGD requires a study of this new nosology and the development of effective prevention and coping strategies. Purpose The purpose of the article is to conduct an analysis of the concept of "prolonged grief disorder" at the current stage, a critical review of modern research on this problem. Methods In order to achieve the goal, a thorough qualitative and quantitative content analysis of the scientific literature devoted to the grieving process and PGD was conducted. The articles search was carried out using international databases such as PubMed, Google Scholar, Web of Science and CrossRef for the period 1997-2024. Conclusions Today there are differences in the definition of PGD. The new clear and unified diagnostic criteria should not only formally lead to understanding of the disorder’s prevalence but also help in the development of diagnostic scales. The accumulation of knowledge in the field of effective treatment of PGD is also ongoing with the aim of further creating unified treatment protocols.